2014
DOI: 10.1016/j.bbrc.2013.12.142
|View full text |Cite
|
Sign up to set email alerts
|

Long-term electrophysiological activity and pharmacological response of a human induced pluripotent stem cell-derived neuron and astrocyte co-culture

Abstract: Human induced pluripotent stem cell (hiPSC)-derived neurons may be effectively used for drug discovery and cell-based therapy. However, the immaturity of cultured human iPSC-derived neurons and the lack of established functional evaluation methods are problematic. We here used a multi-electrode array (MEA) system to investigate the effects of the co-culture of rat astrocytes with hiPSC-derived neurons on the long-term culture, spontaneous firing activity, and drug responsiveness effects. The co-culture facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 21 publications
9
138
2
Order By: Relevance
“…These findings extend data from Dage et al (2014), who showed that iCell neurons respond with robust calcium transients in response to GABA and NMDA exposure up to DIV28. Nevertheless, it is important to characterize any iPSC-derived model and elucidate the receptor profile at different days in culture prior to neurotoxicity testing, as it has been shown that cellular properties can vary over time due to the maturation process of the cells (Odawara et al, 2014;Dage et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings extend data from Dage et al (2014), who showed that iCell neurons respond with robust calcium transients in response to GABA and NMDA exposure up to DIV28. Nevertheless, it is important to characterize any iPSC-derived model and elucidate the receptor profile at different days in culture prior to neurotoxicity testing, as it has been shown that cellular properties can vary over time due to the maturation process of the cells (Odawara et al, 2014;Dage et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, future experiments using human iPSCs should focus on identification of culture conditions that allow bursting behavior and increase MSR as well as the percentage of active wells and the percentage of active electrodes. In this respect it should be noted that co-culturing human iPSC-derived neurons with astrocytes may enhance synaptic maturation and transmission (Clarke and Barres, 2013) as well as firing frequency and bursting behavior (Odawara et al, 2014).…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, protocols used for studying hiPSC-derived neuronal networks with MEAs relied on time-consuming differentiation procedures [13][14][15][16] . The protocol from Zhang et al (2013) provides a rapid alternative, and our modification removes a source of variability, which makes it now more feasible to use hiPSC-derived neurons in combination with MEA technology, especially in highthroughput or pharmacological studies.…”
Section: Establish the Neurophysiological Profile Of Hipsc-derived Nementioning
confidence: 99%